2020
DOI: 10.1145/3377323
|View full text |Cite
|
Sign up to set email alerts
|

A Multilingual Evaluation for Online Hate Speech Detection

Abstract: The increasing popularity of social media platforms such as Twitter and Facebook has led to a rise in the presence of hate and aggressive speech on these platforms. Despite the number of approaches recently proposed in the Natural Language Processing research area for detecting these forms of abusive language, the issue of identifying hate speech at scale is still an unsolved problem. In this article, we propose a robust neural architecture that is shown to perform in a satisfactory way across different langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 34 publications
1
88
0
Order By: Relevance
“…3.3, with Twitter establishing itself as by far the most exploited source. An interesting and promising effort is that by Sabat et al (2019) and, partly, by Corazza et al (2019), who mix up textual and visual data: although still at an early stage, this path could be explored further, given the amount of image-based Table 2 it can be observed that the resources size spans from a few hundreds to several million items: this information correlates with the collection and annotation procedure inasmuch as automatic methods allow for much larger data collection, while human labeling, especially if performed by a few experts, results in smaller dataset and require a greater effort. On the other hand, if many authors prefer to collect finer-grained and higher-quality annotation on smaller samples, this suggests a commitment to creating resources of higher quality, to exploring more complex nuances and to better understand how HS can be framed with NLP techniques.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…3.3, with Twitter establishing itself as by far the most exploited source. An interesting and promising effort is that by Sabat et al (2019) and, partly, by Corazza et al (2019), who mix up textual and visual data: although still at an early stage, this path could be explored further, given the amount of image-based Table 2 it can be observed that the resources size spans from a few hundreds to several million items: this information correlates with the collection and annotation procedure inasmuch as automatic methods allow for much larger data collection, while human labeling, especially if performed by a few experts, results in smaller dataset and require a greater effort. On the other hand, if many authors prefer to collect finer-grained and higher-quality annotation on smaller samples, this suggests a commitment to creating resources of higher quality, to exploring more complex nuances and to better understand how HS can be framed with NLP techniques.…”
Section: Tablementioning
confidence: 99%
“…For example, our survey captures a great availability of benchmark datasets for the evaluation of abusive language and hate speech detection systems, in several languages and with several topical focuses. This adds to the challenge of investigating architectures which are stable and well-performing across different languages and abusive domains, making it a more and more promising topic to research (Corazza et al 2020;Pamungkas and Patti 2019;Ousidhoum et al 2019).…”
Section: Lexical Analysismentioning
confidence: 99%
“…This evaluation gap is being bridged recently by evaluation campaigns for English, Spanish (SemEval [10]), German [11], and Italian (EVALITA [12]), whose shared tasks released annotated datasets for hate speech detection. The availability of benchmarks for system evaluation and datasets for hate speech detection in different languages made the challenge of investigating architectures, which are also stable and well-performing across different languages, an exciting issue to research [13,14].…”
Section: Related Workmentioning
confidence: 99%
“…Paper [17] is about detecting hate speech in social networks. Hate speech increased of attacks targeting spesific groups of users based on their religion, ethnicity, or social status.…”
Section: Resultsmentioning
confidence: 99%